Exploring in vitro and in vivo anti-inflammatory activities of the Thai traditional remedy Kheaw-Hom and its bioactive compound, ethyl p-methoxycinnamate, and ethnopharmacological analysis - Sukkasem K. (2023)
Ethnopharmacological relevance: Kheaw-Hom (KH) remedy, a Thai traditional medicine (TTM) on the National List of Essential Medicines, has long been clinically used to treat fever and inflammation in children. However, no in vitro or in vivo anti-inflammatory or bioactive compound studies are published in the literature. Aims of the study: To explore the in vitro and in vivo anti-inflammatory activities of KH remedy and its bioactive compound and analyze relationships between flavor and ethnopharmacological activities of plant components in KH remedy according to TTM theory. Materials and methods: Ethyl p-methoxycinnamate (EPMC), a bioactive compound of KH remedy was analyzed using high performance liquid chromatography (HPLC). In vitro anti-inflammatory activities of ethanolic extract (KHE), aqueous extract (KHA), acid-hydrolysis of KHA (KHA-h), acid-hydrolysis of KH powder (KHP-h), and EPMC were investigated using lipopolysaccharide (LPS)-induced nitric oxide (NO), prostaglandin E2 (PGE2), and tumor necrosis factor-alpha (TNF-α) production in murine macrophage RAW 264.7 cells. In vivo anti-inflammatory activities of KH powder (KHP) and KHE were determined using carrageenan-induced paw edema and ethyl phenylpropiolate (EPP)-induced ear edema in rats and PGE2 production in tissue samples was examined. Results: KHP-h showed the highest EPMC content (21.33 ± 1.08 mg/g of extract) and inhibited PGE2, NO, and TNF-α production with IC50 values of 11.92 ± 0.21, 30.61 ± 3.12, and 56.71 ± 2.91 μg/mL, respectively, followed by KHE and KHA-h while KHA did not. EPMC, a bioactive compound of KH remedy showed high anti-inflammatory activities through three pathways. KHP oral administration (100 mg/kg) significantly minimized rat paw inflammation at 1, 2, and 3 h while KHE (100 mg/kg) noticeably reduced at 2 and 3 h. KHP (100, 200, and 400 mg/kg) and KHE (100 mg/kg) significantly inhibited PGE2 production. KHP (1% w/v) notably reduced rat ear edema at 30, 60, and 120 min whereas KHE at all concentrations decreased swelling at 120 min. KHP and KHE at all doses significantly inhibited PGE2 production. Cool flavor was the main KH remedy flavor. Spicy plant components and some fragrant components showed high anti-inflammatory activity. Conclusions: Results from the in vivo study strongly paralleled the in vitro study. These findings support the rational use of KH remedy according to TTM theory for fever treatment and inflammation in children.